Komposisi dan Kemelimpahan Jenis Fitoplankton di Perairan Pelabuhan Carik Kecamatan Bayan Kabupaten Lombok Utara - Armiani, Sucika (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2021)
This study aims to determine the composition and abundance of phytoplankton in the waters of Carik Harbor, North Lombok Regency. Research activities include: determining sampling points, taking samples, and measuring water quality (including temperature, pH, salinity, and brightness) at each sampling point and identifying types of phytoplankton. Data were collected by purposive sampling, as many as 7 points in the coastal area of ​​Carik Harbor. Based on the identification results, calculations were made on the composition of the number of species. The results of laboratory observations, found 62 types of phytoplankton from Carik harbor waters from 2 orders, namely: Bacillariophyceae (Diatomae) and Dynophyceae. Species from the order Bacillariophyceae are the most dominating, with 58 species, while from other orders, namely Dynophyceae, there are 4 species. The highest abundance was at station 6 (143080 cells/L) and the lowest was at station 5 (54880 cells/L).